1994
DOI: 10.1128/aac.38.5.969
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal effect of myeloperoxidase on human immunodeficiency virus type 1-infected T cells

Abstract: Myeloperoxidase is virucidal to human immunodeficiency virus type 1 (HIV-1) in the persistently infected CEM human T-cell line or in acutely infected human peripheral blood mononuclear cells, as judged by viral infectivity and P24 radioimmunoassay. HIV-1 was specifically inactivated by low doses of the human myeloperoxidase (1.4 to 14.3 mU/ml) and the cells were spared. A higher enzyme concentration (143 mU/m) was cytotoxic, but uninfected CEM cells and normal lymphocytes were resistant to -143 mU of myelopero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…The antimicrobial activity of myeloperoxidase has been intensively studied in mammalian systems (Klebanoff 1968;Wright et al 1983;Chase and Klebanoff 1992;Chochola et al 1994;Cooray and Björck 1995;Lincoln et al 1995;Hampton et al 1996;Lefkowitz et al 1996). However, few experiments have been conducted to evaluate this enzyme closely for its © 1999 The Society for Applied Microbiology, Journal of Applied Microbiology 86, 211-220 usefulness in controlling plant pathogens (Jacks et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity of myeloperoxidase has been intensively studied in mammalian systems (Klebanoff 1968;Wright et al 1983;Chase and Klebanoff 1992;Chochola et al 1994;Cooray and Björck 1995;Lincoln et al 1995;Hampton et al 1996;Lefkowitz et al 1996). However, few experiments have been conducted to evaluate this enzyme closely for its © 1999 The Society for Applied Microbiology, Journal of Applied Microbiology 86, 211-220 usefulness in controlling plant pathogens (Jacks et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…MPO has three isoenzymes: MPO I, II and III, and plays an important role in the defence mechanism against microorganisms (Wright et al, 1990;Miyasaki et al, 1987;Rocha et al, 2002). This enzyme, purified for the first time by Agner (1941), is one of the important proteins of azurophilic granular leukocytes, is found in their cytoplasm with other antimicrobial proteins and is effective on many micro-organisms, especially viruses (Olsson et al, 2004;Chochola et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…As regards the effect on viruses, native myeloperoxidase puri®ed from neutrophils was shown to inactivate in¯uenza virus [Yamamoto et al, 1991] and HIV-1 virus [Klebanoff and Kazazi, 1995]. Availability of human recombinant form of the enzyme [Moguilevsky et al, 1991] facilitated further studies and demonstrated its virucidal effect on HIV-1 virus [Moguilevsky et al, 1992;Chochola et al, 1994]. To extend results obtained with RNA viruses, myeloperoxidase activity was tested on a DNA virus of the herpesviruses family, namely human cytomegalovirus.…”
Section: Introductionmentioning
confidence: 99%